Maybe ECD kidneys aren't as bad as I thought?. Issue 5 (22nd March 2018) - Englesbe, Michael J.
Abstract : New assessment of extended criteria kidneys in France suggests they should be used more aggressively for recipients. See the article from Querard et al onpage 1151 .